Extraction Behavior of REEs (La, Pr, and Nd) in the Presence of EDTA from Chloride Solutions - Banda, Raju; Jeon, Ho Seok; Lee, Man Seung (Korean Journal Metals and Materals, 2013)
Extraction behavior of REEs (La, Pr, and Nd) from chloride solutions is investigated using Cyanex 272 and PC 88A. PC 88A had a greater extraction efficiency towards REEs than Cyanex 272. Adding EDTA to the aqueous solution depressed the extraction of Pr and Nd due to the formation of anionic complexes and had a negative effect on the separation of La from Nd and Pr. The extraction behavior of REEs in the presence of EDTA depended on the nature of the extractant. Extraction by Cyanex 272 in the absence of EDTA was better for separating La than extraction by PC 88A. KCI Citation Count: 11